O efeito de dois protocolos de teste incremental nas respostas cardiorrespiratórias em usuários de cadeira de rodas de propulsão manual - Arruda Neto, José Eduardo (2018)
Physical activity is one of the main ways to promote improvement in the quality of life of people who use manual wheelchairs for their movement. For this, it is very important to develop adequate equipment and use principles, methodologies and protocols specifically targeted to this population. The development of specific protocols for the evaluation of the cardiorespiratory response in this population becomes essential, since they are generally adapted from conventional protocols and equipment for people with disabilities. Thus, the objective of the study was to compare oxygen consumption, pulmonary ventilation, carbon dioxide production and heart rate during an incremental test performed on a wheelchair ergometer with duration of 12 minutes in increments every 2 minutes , using two methodologies of increments: In the first one, the rotation of the hoops was kept constant and the torque was increased; in the second, the torque was kept constant and the rotation of the hoops was increased, and the power value was maintained the same for each level determined in the first methodology. Seven athletes who use the manual wheelchair, weightlifters and athletics participated in the study. The results of the experiments showed that in the rotating test, the VO2 (ml / min) (V = 0.000016), VE (L / min) = p <0.05 and VCO2 (ml / min) ) = p <0.05, while heart rate did not show significant differences. The study showed that the behavior of VO2, VE and VCO2 during the tests showed similar characteristics. There was a greater demand in the TC test compared to the RC test, the variables showed a more marked curve in the TC test. In general, there was a higher volume of VO2 and VE and a lower VCO2 in the TC test. The heart rate showed no difference in the RC and CT tests, indicating that the rotation of the rim did not influence this cardiorespiratory parameter.